SDL 2013: model-driven dependability engineering : 16th International SDL Forum, Montreal, Canada, June 26-28, 2013. Proceedings - Toeroe, Maria; Gherbi, Abdelouahed; Reed, Rick; Khendek, Ferhat (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 16th System Design Languages Forum, SDL 2013, held in Montreal, QC, Canada, in June 2013. The 16 revised, high-quality, full papers presented were carefully reviewed and selected from 30 submissions. The papers are organized in topical sections on verification and testing; dependability engineering; analysis; domain specific languages; model transformation; specification and description language and evolution.